The Paleogene and Neogene of Western Iberia (Portugal) A Cenozoic record in the European Atlantic domain - Pais, João (SpringerBriefs in Earth Sciences, 2012)
The book includes a general description of the Portuguese Cenozoic basins in the Iberian tectonic context. The main stratigraphic units, including sedimentological, stratigraphical and palaeontological data, are characterized. Correlations between different sectors are presented as well as general paleogeographical evolution maps. The volume includes a general bibliography concerning the Cenozoic of Portugal.